The golden ratio and Viéte’s formula - García-Caballero, Esther M.; Moreno, Samuel G.; Prophet, Michael P. (Teaching Mathematics and Computer Science, 2014)
Viéte's formula uses an infinite product to express. In this paper we find a strikingly similar representation for the Golden Ratio.